(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the motives of the perpetrators of criminal acts of fraud with the mode of Social Gathering through social media. And to know and analyze the efforts made by law enforcers to tackle criminal acts of fraud with arisan mode through social media in Makassar City. This research uses empirical research methods. Data collection methods are carried out using field studies and literature studies by means of interviews. The data is processed systematically, factually, and accurately and analyzed qualitatively and presented descriptively. The results of this study indicate that the motive of the perpetrators of criminal fraud with Social Gathering mode through social media in Makassar city is due to the motive of wanting to get rich instantly by deceiving others (financial motive), the cultural motive of people who are less careful on social media and lack of knowledge of fraud crimes with online arisan mode. The efforts made by law enforcers to tackle criminal acts of fraud with arisan mode through social media in Makassar City are carried out with two efforts, namely: Preventive efforts and repressive efforts. Based on the results of this study, it is recommended that the local government of Makassar City cooperate with the police and social media platform providers to improve public digital literacy, strengthen regulations related to online fraud, and increase the capacity of law enforcement in handling similar cases. In addition, it is necessary to establish a special legal aid center to provide legal assistance for victims of arisan fraud through social media. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis motif pelaku tindak pidana penipuan dengan modus arisan melaui media sosial. Serta Untuk mengetahui dan menganalisis upaya yang dilakukan penegak hukum untuk menanggulangi tindak pidana penipuan dengan modus arisan melaui media sosial di Kota Makassar. Penelitian ini menggunakan metode penelitian empiris. Metode pengumpulan data dilakukan menggunakan studi lapangan dan studi kepustakaan dengan cara wawancara. Data diolah secara sistematis, faktual, dan akurat serta dianalisis secara kualitatif dan disajikan secara deskriptif. Hasil penelitian ini menunjukkan motif pelaku tindak pidana penipuan dengan modus arisan melalui media sosial di kota Makassar ialah dikarenakan motif ingin menjadi kaya secara instan dengan cara menipu orang lain (motif finansial), motif budaya masyarakat yang kurang berhati-hati di media sosial dan kurangnya pengetahuan terhadap kejahatan penipuan dengan modus arisan online. Adapun upaya yang dilakukan penegak hukum untuk menanggulangi tindak pidana penipuan dengan modus arisan melaui media sosial di Kota Makassar dilakukan dengan dua upaya yaitu: upaya preventif dan upaya represif. Berdasarkan hasil penelitian ini, disarankan agar pemerintah daerah Kota Makassar bekerja sama dengan pihak kepolisian dan penyedia platform media sosial untuk meningkatkan literasi digital masyarakat, memperkuat regulasi terkait tindak pidana penipuan online, serta meningkatkan kapasitas penegak hukum dalam menangani kasus serupa. Selain itu, perlu dibentuk pusat bantuan hukum khusus untuk memberikan pendampingan hukum bagi korban penipuan arisan melaui media sosial.